Peran Psikologi Pendidikan dalam Penguatan Kesiapan Guru di Era Digital melalui Pelatihan Active Learning, Student-Centered Learning, dan Jigsaw Learning - Hanida Alifiyah; Nur Aisyah; Eugin Dara Mentari; Paramitha Mei Dianti; Muhammad Tomi Nizam; Fajar Tri Utami; Chintia Viranda (CV. Doki Course and Training, 2026)
The rapid development of digital technology has transformed educational practices, requiring teachers to adapt to more student-centered, collaborative, and technology-integrated learning approaches. However, teacher readiness in implementing active and innovative learning strategies remains a challenge in many educational settings. This study aimed to describe the role of educational psychology in strengthening teacher readiness in the digital era through training based on Active Learning, Student-Centered Learning (SCL), and Jigsaw Learning for teachers at Yayasan Perguruan Islam Ummul Quro’ Al-Hamidiyah Palembang. This study employed a descriptive evaluative approach with qualitative support and simple quantitative data. The participants consisted of 22 teachers who attended the training on May 2, 2026. Data were collected through observation, facilitator field notes, and participant evaluation during the training process. The findings indicated positive changes in teacher readiness, particularly in self-confidence, analytical skills, participation in discussions, and readiness to implement learning strategies in classroom settings. Evaluation results showed that teachers’ theoretical understanding reached 95%, digital literacy 92%, and practical readiness 88%. The integration of Active Learning, Student-Centered Learning, and Jigsaw Learning encouraged active participation, reflective thinking, collaboration, and communication among participants. The study concludes that educational psychology-based training contributes to strengthening teacher readiness in the digital era by enhancing theoretical understanding, digital literacy, and practical teaching readiness. Future studies are recommended to involve broader participants and longer implementation periods to evaluate the sustainability of training outcomes in classroom practice.